Sort by

- Relevance
- |Time

...)/ (x^2+1)^2 Then multiply all terms by the denominator of the

**LHS**, and equate coefficients for each separate power of x. I admit this...2 Answers · Science & Mathematics · 23/12/2013

...the ODE becomes x^2 y^4 dx + 2x^3 y^3 dy = 0, but this time, the

**LHS**isn't an exact differential, so this expression (x^2 y^3) didn't turn out to be...1 Answers · Science & Mathematics · 03/12/2013

... obvious, just divide RHS by the bracketed coefficient from the

**LHS**.1 Answers · Science & Mathematics · 25/11/2013

...: tan² θ cos² θ + cot² θ sin²θ = 1

**LHS**= (sin²θ/cos²θ) × cos² θ+ (cos²θ/sinθ²...1 Answers · Science & Mathematics · 01/10/2013

...u+1)/u u du/(u+1) = dx Now it's separated; to integrate the

**LHS**, let v=u+1, so (1 - 1/v) dv = dx v - ln|v| = x + C1 u - ln|u+1| = x + ...2 Answers · Science & Mathematics · 02/10/2013

**LHS**: F=m.a =kg. m/s2 =ML/T2 RHS: rho=kg/m3 g =m/s2 V=m3 Multiplying these, F=kg.m/s2 =ML/T2 Thus, RHS=**LHS**Hence the proof!1 Answers · Science & Mathematics · 03/09/2013

...of the RHS is obviously ln(x) + C. Integral of the

**LHS**looks tough, trying Wolfram Integrator if you'...1 Answers · Science & Mathematics · 03/07/2013

...91 is a transformation of Eqn 2-88, using 2-89 to replace the

**LHS**and using 2.90 to replace the RHS of 2-88. Eqn 2-92 ...1 Answers · Science & Mathematics · 26/05/2013

...x) - cos(x)/sin(x) = tan(x) - cot(x) But now it's perfectly clear that the

**LHS**equals the RHS.1 Answers · Science & Mathematics · 23/04/2013

... should check this back to see that it satisfies the differential equation (

**LHS**) but no time I'm afraid! We now have to find any particular solution...2 Answers · Science & Mathematics · 19/03/2013

##### Ad

related to**LHS**